2013
DOI: 10.1016/j.neuron.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Directed Migration of Cortical Interneurons Depends on the Cell-Autonomous Action of Sip1

Abstract: GABAergic interneurons mainly originate in the medial ganglionic eminence (MGE) of the embryonic ventral telencephalon (VT) and migrate tangentially to the cortex, guided by membrane-bound and secreted factors. We found that Sip1 (Zfhx1b, Zeb2), a transcription factor enriched in migrating cortical interneurons, is required for their proper differentiation and correct guidance. The majority of Sip1 knockout interneurons fail to migrate to the neocortex and stall in the VT. RNA sequencing reveals that Sip1 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 64 publications
2
122
0
Order By: Relevance
“…In support of these findings, a similar study reported reduced cortical GABAergic interneurons, downregulation of cortical interneuron markers (including cMaf and Cxcr7) and increased Nkx2.1 expression, in mice with conditional knockout of Zeb2 in the MGE . The study by van den Berghe et al (2013) demonstrated that Zeb2 directly regulates the cortical migration of MGE-derived GABAergic interneurons, which express high levels of Zeb2. Zeb2 was shown to act cell-autonomously to direct cortical interneuronal migration through regulation of the precise levels of the Unc5b netrin-repulsive receptor, with Unc5b knockout also being shown to rescue the migration defect of the Zeb2 mutant mice .…”
Section: Zeb2 In Cerebral Developmentmentioning
confidence: 99%
“…In support of these findings, a similar study reported reduced cortical GABAergic interneurons, downregulation of cortical interneuron markers (including cMaf and Cxcr7) and increased Nkx2.1 expression, in mice with conditional knockout of Zeb2 in the MGE . The study by van den Berghe et al (2013) demonstrated that Zeb2 directly regulates the cortical migration of MGE-derived GABAergic interneurons, which express high levels of Zeb2. Zeb2 was shown to act cell-autonomously to direct cortical interneuronal migration through regulation of the precise levels of the Unc5b netrin-repulsive receptor, with Unc5b knockout also being shown to rescue the migration defect of the Zeb2 mutant mice .…”
Section: Zeb2 In Cerebral Developmentmentioning
confidence: 99%
“…We have read with interest the latest advances regarding ZEB2 gene function in neuroembryology and its connections with epilepsy (McKinsey et al, 2013;Van den Berghe et al, 2013). Zinc finger E-box binding homeobox 2 (ZEB2, MIM#60580), also annotated as ZFHX1B and SIP1, is a member of the two-handed zinc finger/homeodomain transcription factors.…”
Section: To the Editorsmentioning
confidence: 99%
“…45,46 Melanin content determination. Melanin was extracted with an alkaline solution as previously described.…”
mentioning
confidence: 99%